Stainless steel composite patterned plate with anti-skid and wear-resistant surface

CN224868016UActive Publication Date: 2026-10-20连云港永誉不锈钢制品有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522405851.0
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-11-13
Publication Date
2026-10-20
Estimated Expiration
2035-11-13

AI Technical Summary

Technical Problem

[0008]针对现有技术的不足,本实用新型提供了一种具有防滑耐磨表面的不锈钢复合花纹板,解决了现有不锈钢板材在潮湿/油污环境下防滑性能不足、耐磨性能有限导致寿命短、层间结合不牢固易分层及花纹稳定性差易变形脱落的技术问题

Benefits of technology

[0022]表面功能层的菱形花纹形成基础防滑结构,可增大接触面摩擦系数;交叉处的半球形凹坑能储存水、油等液体,避免形成润滑膜,二者配合实现干燥-潮湿-油污多场景稳定防滑,摩擦系数范围达0.68-0.88,远高于传统不锈钢板(0.4-0.6),有效降低安全风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224868016U_ABST
    Figure CN224868016U_ABST
Patent Text Reader

Abstract

The utility model relates to stainless steel composite patterned plate technical field, especially disclose a kind of stainless steel composite patterned plate with antiskid wear-resistant surface, to solve the problem of existing stainless steel plate skid, wear limited, interlayer easy delamination. The composite patterned plate from bottom to top includes base layer, transition layer, surface functional layer, three layers are connected by hot-pressing composite process, and set reinforcing connection structure;Base layer is low-carbon steel base plate, lower surface is provided with strip-shaped groove, upper surface is provided with dovetail groove;Transition layer is nickel-chromium alloy layer, lower surface is provided with dovetail block compatible with dovetail groove, upper surface is provided with four groups of conical protrusions;Surface functional layer is martensitic stainless steel layer, upper surface is provided with diamond pattern with included angle 60 ° and hemispherical pit at intersection, surface is sprayed with nano ceramic wear-resistant coating;Reinforcing connection structure further includes titanium alloy metal connecting column between transition layer and surface functional layer. The utility model is connected by mortise and tenon+embedded type through double antiskid structure, double wear protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the technical field of stainless steel composite patterned plates, and in particular to a stainless steel composite patterned plate with a non-slip and wear-resistant surface. Background Technology

[0002] Stainless steel sheets are widely used in building decoration (stair treads, flooring), transportation (vehicle floors, ship decks), and machinery manufacturing (work surfaces) due to their strong corrosion resistance and clean appearance. However, existing stainless steel sheets have the following key technical defects in practical use:

[0003] Insufficient anti-slip performance: Traditional stainless steel plates are mostly smooth or have a single unidirectional pattern. In humid (rainy days, bathrooms) or oily (workshops, kitchens) environments, liquids easily form a continuous lubricating film on the surface, resulting in a significant decrease in the coefficient of friction (the coefficient of friction is about 0.6 in a dry environment and drops to below 0.4 in a humid environment), which poses a very high safety risk of people slipping and goods sliding.

[0004] Limited wear resistance: Ordinary stainless steel has a low surface hardness (HV200-300), and after long-term use, it is prone to scratches and pattern wear, which not only damages the appearance, but also further weakens the anti-slip function. Its service life is usually only 1-2 years.

[0005] Weak interlayer bonding: Most existing composite stainless steel plates adopt a simple lamination process without dedicated reinforcing connection structure between layers. Under the influence of temperature changes (thermal expansion and contraction) or long-term stress, delamination is prone to occur, leading to the failure of the overall structure.

[0006] Poor pattern stability: The pattern on some patterned boards is formed only by surface pressing, resulting in low bonding strength with the substrate. After long-term friction, the pattern is prone to deformation and falling off, failing to continuously guarantee the anti-slip effect.

[0007] The aforementioned defects make it difficult for existing stainless steel sheets to meet the requirements of high slip resistance, high wear resistance, and long service life. There is an urgent need to design a composite patterned sheet with optimized structure to solve the above technical problems simultaneously. Utility Model Content

[0008] To address the shortcomings of existing technologies, this utility model provides a stainless steel composite patterned plate with an anti-slip and wear-resistant surface, which solves the technical problems of insufficient anti-slip performance, limited wear resistance leading to short lifespan, weak interlayer bonding causing easy delamination, and poor pattern stability causing easy deformation and detachment of existing stainless steel plates in humid / oily environments.

[0009] To achieve the above objectives, this utility model provides the following technical solution:

[0010] A stainless steel composite patterned plate with a non-slip and wear-resistant surface includes a base layer, a transition layer and a surface functional layer arranged sequentially from bottom to top.

[0011] The base layer, transition layer and surface functional layer are fixedly connected by a hot-pressing composite process, and a reinforcing connection structure is provided between the three.

[0012] The base layer is a low-carbon steel substrate with a thickness of 3-8mm. The lower surface of the base layer is provided with several strip-shaped grooves evenly distributed along its length.

[0013] The transition layer is a nickel-chromium alloy layer with a thickness of 0.5-1.5 mm. Four sets of equidistant arrays of conical protrusions are evenly distributed on the upper surface of the transition layer.

[0014] The surface functional layer is a martensitic stainless steel layer with a thickness of 1-3mm. The upper surface of the surface functional layer is provided with a cross-grid distributed diamond pattern, and a hemispherical pit is provided at the intersection of the diamond pattern.

[0015] The enhanced connection structure includes four dovetail grooves on the upper surface of the base layer, four dovetail blocks on the lower surface of the transition layer that are adapted to the dovetail grooves, and three sets of metal connecting columns between the transition layer and the surface functional layer. The two ends of the metal connecting columns are embedded in the transition layer and the surface functional layer, respectively.

[0016] Preferably, the surface functional layer is further coated with a nano-ceramic wear-resistant coating that covers diamond patterns and hemispherical pits, and the thickness of the nano-ceramic wear-resistant coating is 50-100μm.

[0017] Preferred: The included angle of the rhombus pattern is 60°.

[0018] Preferably, the metal connecting column is made of titanium alloy.

[0019] Preferably, the top of the conical protrusion has a rounded chamfer.

[0020] Preferably, the material of the nano-ceramic wear-resistant coating is alumina-zirconia composite ceramic, and the hardness of the nano-ceramic wear-resistant coating is not less than HV1500.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The diamond-shaped pattern on the surface functional layer forms a basic anti-slip structure, which can increase the friction coefficient of the contact surface; the hemispherical pits at the intersections can store liquids such as water and oil, preventing the formation of a lubricating film. The two work together to achieve stable anti-slip in multiple scenarios such as dry, wet and oily, with a friction coefficient ranging from 0.68 to 0.88, which is much higher than that of traditional stainless steel plates (0.4-0.6), effectively reducing safety risks.

[0023] The surface functional layer uses high-hardness martensitic stainless steel (HV500-550) as the base material, combined with an alumina-zirconia composite ceramic coating (HV≥1500) sprayed on the surface, forming a double wear-resistant protection; verified by Taber wear resistance test (grinding wheel CS-10, load 1000g), the pattern wear after 50,000 friction cycles is only 0.05-0.06mm, and the service life can reach 5-8 years, which is 3-4 times that of traditional stainless steel plates, greatly reducing replacement and maintenance costs;

[0024] The base layer and the transition layer are prevented from separating laterally through the mortise and tenon structure of dovetail groove and dovetail block. The transition layer and the surface functional layer are connected vertically by titanium alloy metal connecting columns. The double-reinforced connection structure makes the interlayer peel strength reach 25-32MPa. There is no delamination after long-term stress or temperature change, ensuring the stability of the overall structure.

[0025] The grooved strips on the lower surface of the base layer can form an interlocking structure with adhesives and installation parts, with no displacement under a horizontal thrust of 5000N, and are suitable for various installation surfaces such as concrete and metal; the thickness of each layer (base layer: 3-8mm, transition layer: 0.5-1.5mm, surface functional layer: 1-3mm) can be adjusted according to the scenario, meeting the needs of medium and heavy load scenarios such as stair treads, as well as light load scenarios such as interior decoration, and covering multiple fields such as construction, transportation, and machinery;

[0026] The conical protrusions support the surface functional layer to prevent pattern deformation without damaging the interlayer connection; the nano-ceramic coating completely covers the pattern and pits without affecting the anti-slip structure; the overall design takes into account both functionality and process feasibility, and can be mass-produced using existing hot pressing and spraying equipment, thus possessing good industrialization and promotion value. Attached Figure Description

[0027] The above description is only an overview of the technical solution of this utility model. In order to better understand the technical means of this utility model and to implement it in accordance with the contents of the specification, the preferred embodiments of this utility model are described in detail below with reference to the accompanying drawings.

[0028] Figure 1 This is a schematic diagram showing the location of the nano-ceramic wear-resistant coating in this utility model;

[0029] Figure 2 This is a structural diagram of the rhombus pattern in this utility model;

[0030] Figure 3 This is a structural diagram of the metal connecting column in this utility model;

[0031] Figure 4 This is a structural diagram of the dovetail block in this utility model.

[0032] Legend: 1. Base layer; 2. Transition layer; 3. Surface functional layer; 4. Strip groove; 5. Conical protrusion; 6. Diamond pattern; 7. Hemispherical pit; 8. Dovetail groove; 9. Dovetail block; 10. Metal connecting column; 11. Nano-ceramic wear-resistant coating. Detailed Implementation

[0033] This application provides a stainless steel composite patterned plate with a non-slip and wear-resistant surface, which effectively solves the technical problems of existing stainless steel plates, such as insufficient non-slip performance, limited wear resistance leading to short life, weak interlayer bonding causing easy delamination, and poor pattern stability causing easy deformation and detachment in humid / oily environments.

[0034] Example

[0035] like Figure 1 , Figure 2 , Figure 3 and Figure 4 As shown, the overall technical solution in this application embodiment is as follows:

[0036] To address the problems existing in the prior art, this utility model provides a stainless steel composite patterned plate with an anti-slip and wear-resistant surface. The aim is to provide a stainless steel composite patterned plate with excellent anti-slip and wear-resistant properties and a stable interlayer structure. Through layered design and reinforced connection structure, it solves the problems of insufficient anti-slip properties, limited wear resistance, and easy delamination between layers in traditional stainless steel plates. Its core technical content is as follows:

[0037] It adopts a three-layer composite structure from bottom to top: base layer 1 → transition layer 2 → surface functional layer 3. The three layers are connected as a whole through hot pressing composite process. At the same time, it is equipped with a special reinforced connection structure to ensure that there is no relative displacement or delamination between the layers. The overall structure takes into account the support strength, functional adaptability and installation stability.

[0038] The base layer 1 is made of low-carbon steel substrate with a thickness of 3-8mm (which can be adjusted according to the scenario: 6-8mm for heavy-load scenarios and 3-5mm for light-load scenarios), providing high support strength. The lower surface is machined with strip grooves 4 that are evenly distributed along the length direction to enhance the bonding stability with the mounting surface (concrete, metal brackets, etc.), and slippage is prevented by filling with adhesive or interlocking with mounting parts. The upper surface is machined with four dovetail grooves 8 (arranged at the four corners) as the connection base with the transition layer 2.

[0039] The transition layer 2 is made of nickel-chromium alloy with a thickness of 0.5-1.5mm. It utilizes its good bonding properties with low carbon steel and martensitic stainless steel to solve the material compatibility problem between the base layer 1 and the surface functional layer 3.

[0040] Four dovetail blocks 9 are machined on the lower surface to perfectly fit the dovetail groove 8 of the base layer 1, so as to achieve a lateral anti-separation connection with the base layer 1. The irregular shape of the dovetail blocks 9 also facilitates positioning.

[0041] The upper surface is machined with four sets of equidistant arrays of conical protrusions 5, with rounded chamfers at the top. This not only avoids scratching the surface functional layer 3, but also provides multi-point support for the surface functional layer 3, preventing deformation of the weak areas of the structure due to the pattern processing.

[0042] The surface functional layer 3 is made of martensitic stainless steel with a thickness of 1-3mm, utilizing its high hardness (HV500-550) as the basis for wear resistance.

[0043] The upper surface is machined with a cross-grid diamond pattern 6, with an included angle of 60°, which increases the friction coefficient of the contact surface to achieve basic anti-slip;

[0044] At the intersection of the diamond pattern 6, a hemispherical recess 7 is processed to store liquids such as water and oil, so as to prevent the formation of a lubricating film that would cause the anti-slip effect to fail.

[0045] The surface is sprayed with a nano-ceramic wear-resistant coating 11 (material is alumina-zirconia composite ceramic, thickness 50-100μm, hardness ≥HV1500), which further improves the surface wear resistance and scratch resistance.

[0046] The base layer 1 and the transition layer 2 are connected by mortise and tenon joints of dovetail groove 8 and dovetail block 9 to prevent lateral separation, and the peel strength can reach more than 30MPa;

[0047] Three sets of metal connecting pillars 10 (made of titanium alloy TC4) are evenly distributed along the length direction between the transition layer 2 and the surface functional layer 3. The two ends of the connecting pillars are embedded in the transition layer 2 and the surface functional layer 3 respectively to enhance the vertical bonding strength and avoid interlayer delamination.

[0048] The dual structure of diamond-shaped pattern 6 (basic friction) + hemispherical pit 7 (liquid storage and anti-lubrication) achieves stable anti-slip in multiple scenarios such as dry, wet and oily conditions, with the coefficient of friction maintained at 0.68-0.88;

[0049] The combination of martensitic stainless steel substrate (basic wear resistance) and nano-ceramic coating (enhanced wear resistance) results in a pattern wear of ≤0.06mm after 50,000 friction tests.

[0050] The groove 4 of the base layer 1 is suitable for various installation methods, and its anti-slip capability meets the requirement of no displacement under a horizontal thrust of 5000N.

[0051] Example 1 (Applicable to medium to heavy load scenarios: such as stair treads, workshop floors):

[0052] Structural parameters:

[0053] Base layer 1: Q235 low carbon steel, 5mm thick; 4 strip grooves (groove width 3mm, groove depth 0.8mm, adjacent spacing 12mm); 8 dovetail grooves (groove opening width 15mm, groove depth 5mm, adjacent spacing 10mm); surface sandblasting treatment (roughness Ra1.6μm);

[0054] Transition layer 2: Inconel 600 nickel-chromium alloy, 1mm thick; dovetail block 9 (fitting dovetail groove 8); conical protrusion 5 (height 0.5mm, chamfer radius 0.15mm, spacing between each array 5mm); surface polishing treatment (roughness Ra0.8μm);

[0055] Surface functional layer 3: 440C martensitic stainless steel, 2mm thick; diamond pattern 6 (60° included angle, 8mm side length, 1.0mm depth); hemispherical pit 7 (1.2mm diameter); surface passivation treatment;

[0056] Reinforced connection structure: 10 titanium alloy metal connecting posts (0.3 mm in diameter, 8 mm spacing between adjacent groups, and 0.5 mm embedment depth each); 11 nano-ceramic wear-resistant coating (80 μm thick, HV1600).

[0057] Preparation process:

[0058] Step 1: Pre-processing: CNC milling of base layer 1 strip groove 4 and dovetail groove 8, forging of transition layer 2 dovetail block 9, stamping of conical protrusion 5, rolling + laser engraving of surface functional layer 3 patterns and pits;

[0059] Step 2: Connecting post assembly: Drill blind holes (0.3mm in diameter and 0.5mm in depth) at the corresponding positions of the transition layer 2 and the surface functional layer 3, apply BNi-2 brazing flux, and insert the titanium alloy connecting post;

[0060] Step 3: Hot pressing composite: Stack the base layer 1 → transition layer 2 → surface functional layer 3 (dovetail block 9 is embedded in dovetail groove 8), hot press furnace parameters (temperature 950℃, pressure 20MPa, heat preservation 30min), cool to room temperature;

[0061] Step 4: Coating spraying: Plasma spraying of nano-ceramic coating, sintering at 300℃ for 1 hour, and grinding and trimming the edges.

[0062] Performance test results:

[0063] Anti-slip performance: coefficient of friction is 0.88 in dry environment, 0.75 in wet environment, and 0.68 in oily environment;

[0064] Wear resistance: After 50,000 cycles of Taber test (CS-10 grinding wheel, 1000g load), the pattern wear was 0.05mm, and the coating did not peel off;

[0065] Interlayer performance: peel strength of base layer 1-transition layer 2 is 32 MPa, peel strength of transition layer 2-surface functional layer 3 is 28 MPa;

[0066] Installation performance: Epoxy adhesive installation, no displacement under horizontal thrust of 5000N.

[0067] Example 2 (Applicable to light-load scenarios: such as interior decorative walls, lightweight equipment panels):

[0068] Structural parameters:

[0069] Base layer 1: Q235 low carbon steel, 3mm thick; 4 strip grooves (groove width 2mm, groove depth 0.5mm, adjacent spacing 10mm); 8 dovetail grooves (groove opening width 12mm, groove depth 4mm);

[0070] Transition layer 2: Inconel 600 nickel-chromium alloy, 0.5 mm thick; 5 tapered protrusions (0.3 mm high, 4 mm array spacing);

[0071] Surface functional layer 3: 440C martensitic stainless steel, 1mm thick; diamond pattern 6 (side length 5mm, depth 0.5mm); hemispherical pit 7 (diameter 0.8mm);

[0072] Reinforced connection structure: titanium alloy connecting post 10 (diameter 0.2mm, adjacent group spacing 6mm); nano-ceramic coating 11 (thickness 50μm, HV1500).

[0073] Performance test results:

[0074] Anti-slip performance: 0.85 in dry environment, 0.72 in wet environment;

[0075] Wear resistance: After 50,000 friction tests, the wear amount of the pattern is 0.06 mm;

[0076] Interlayer properties: Peel strength 25 MPa;

[0077] It meets the decoration and basic protection needs of light-load scenarios, and its weight is reduced by 30% compared with Example 1, making it suitable for lightweight installation.

[0078] Finally, it should be noted that the above embodiments are merely examples for clearly illustrating the present invention and are not intended to limit the implementation. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the protection scope of this invention.

Claims

1. A stainless steel composite patterned plate with an anti-slip and wear-resistant surface, characterized in that, It includes a base layer (1), a transition layer (2), and a surface functional layer (3) arranged sequentially from bottom to top; The base layer (1), transition layer (2) and surface functional layer (3) are fixedly connected by hot pressing composite process, and a reinforcing connection structure is provided between the three. The base layer (1) is a low carbon steel substrate with a thickness of 3-8mm. The lower surface of the base layer (1) is provided with several strip grooves (4) evenly distributed along its length. The transition layer (2) is a nickel-chromium alloy layer with a thickness of 0.5-1.5 mm. Four sets of equidistant arrays of conical protrusions (5) are evenly distributed on the upper surface of the transition layer (2). The surface functional layer (3) is a martensitic stainless steel layer with a thickness of 1-3 mm. The surface functional layer (3) has a cross-grid distributed diamond pattern (6) on its upper surface, and a hemispherical pit (7) is provided at the intersection of the diamond pattern (6). The enhanced connection structure includes four dovetail grooves (8) set on the upper surface of the base layer (1), four dovetail blocks (9) set on the lower surface of the transition layer (2) and adapted to the dovetail grooves (8), and three sets of metal connecting columns (10) set between the transition layer (2) and the surface functional layer (3). The two ends of the metal connecting columns (10) are embedded in the transition layer (2) and the surface functional layer (3), respectively.

2. The stainless steel composite patterned plate with an anti-slip and wear-resistant surface according to claim 1, characterized in that, The surface functional layer (3) is also sprayed with a nano-ceramic wear-resistant coating (11) covering the diamond pattern (6) and hemispherical pits (7), and the thickness of the nano-ceramic wear-resistant coating (11) is 50-100μm.

3. The stainless steel composite patterned plate with an anti-slip and wear-resistant surface according to claim 2, characterized in that, The included angle of the rhombus pattern (6) is 60°.

4. The stainless steel composite patterned plate with an anti-slip and wear-resistant surface according to claim 3, characterized in that, The metal connecting column (10) is made of titanium alloy.

5. The stainless steel composite patterned plate with an anti-slip and wear-resistant surface according to claim 4, characterized in that, The top of the conical protrusion (5) has a rounded chamfer.

6. The stainless steel composite patterned plate with an anti-slip and wear-resistant surface according to claim 5, characterized in that, The nano-ceramic wear-resistant coating (11) is made of alumina-zirconia composite ceramic, and the hardness of the nano-ceramic wear-resistant coating (11) is not less than HV1500.